Interaction and uptake of exosomes by ovarian cancer cells - Altevogt Peter (BMC Cancer, 2011)
Abstract Background Exosomes consist of membrane vesicles that are secreted by several cell types, including tumors and have been found in biological fluids. Exosomes interact with other cells and may serve as vehicles for the transfer of protein and RNA among cells. Methods SKOV3 exosomes were labelled with carboxyfluoresceine diacetate succinimidyl-ester and collected by ultracentrifugation. Uptake of these vesicles, under different conditions, by the same cells from where they originated was monitored by immunofluorescence microscopy and flow cytometry analysis. Lectin analysis was performed to investigate the glycosylation properties of proteins from exosomes and cellular extracts. Results In this work, the ovarian carcinoma SKOV3 cell line has been shown to internalize exosomes from the same cells via several endocytic pathways that were strongly inhibited at 4°C, indicating their energy dependence. Partial colocalization with the endosome marker EEA1 and inhibition by chlorpromazine suggested the involvement of clathrin-dependent endocytosis. Furthermore, uptake inhibition in the presence of 5-ethyl-N-isopropyl amiloride, cytochalasin D and methyl-beta-cyclodextrin suggested the involvement of additional endocytic pathways. The uptake required proteins from the exosomes and from the cells since it was inhibited after proteinase K treatments. The exosomes were found to be enriched in specific mannose- and sialic acid-containing glycoproteins. Sialic acid removal caused a small but non-significant increase in uptake. Furthermore, the monosaccharides D-galactose, α-L-fucose, α-D-mannose, D-N-acetylglucosamine and the disaccharide β-lactose reduced exosomes uptake to a comparable extent as the control D-glucose. Conclusions In conclusion, exosomes are internalized by ovarian tumor cells via various endocytic pathways and proteins from exosomes and cells are required for uptake. On the other hand, exosomes are enriched in specific glycoproteins that may constitute exosome markers. This work contributes to the knowledge about the properties and dynamics of exosomes in cancer.